1977
DOI: 10.1161/01.str.8.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Role of the carotid body in speeding the cerebrovascular response to altered PaCO2 in baboons.

Abstract: SUMMARYThe alterations in cerebral perfusion with graded hypercapnia were measured in the baboon using the intra-carotid 1M xenon clearance technique. In addition, the tidal percent of COj and the blood flow in the common carotid artery were measured using a capnograph and an electromagnetic flowmeter respectively. The delay times between the induced increments in tidal respiratory percent of CO] and the beginning of the blood flow increments were assessed, together with the rate of increment of the blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…More explicitly, if increases in CO 2 at the carotid body cause reflex increases in sympathetic outflow that reduce brain blood flow, then CBX would eliminate this reflex sympathetic outflow, allowing for greater increases in brain blood flow during the rebreathe tests, which would blunt the rise in brain tissue PCO 2 compared with the intact responses. It is unlikely, however, that this mechanism explains our findings because it has been demonstrated that CBX does not affect the cerebral blood flow response to inspired CO 2 in the awake baboon (19).…”
Section: Limitationsmentioning
confidence: 65%
“…More explicitly, if increases in CO 2 at the carotid body cause reflex increases in sympathetic outflow that reduce brain blood flow, then CBX would eliminate this reflex sympathetic outflow, allowing for greater increases in brain blood flow during the rebreathe tests, which would blunt the rise in brain tissue PCO 2 compared with the intact responses. It is unlikely, however, that this mechanism explains our findings because it has been demonstrated that CBX does not affect the cerebral blood flow response to inspired CO 2 in the awake baboon (19).…”
Section: Limitationsmentioning
confidence: 65%
“…26 ' 3031 ' 43 ' 47 These data also indicate that two kinds of CO 2 -CBF regulation exist, as was previously supposed. ' 45 It seems reasonable to assume that when neural regulation becomes damaged for various reasons, the direct effect of tissue Pco 2 on the vessel wall takes over.…”
mentioning
confidence: 99%